Preparation method of high-temperature-resistant nanofiber acoustoelectric material and flexible high-temperature sound generator

The TS-PAN nanofiber membrane prepared through multi-step heat treatment solves the problem that existing high-temperature piezoelectric materials fail to achieve acousto-electric conversion at high temperatures, and realizes the acousto-electric conversion capability at high temperatures, which is suitable for various high-temperature acoustics. Electric energy harvesting applications.

CN119433827APending Publication Date: 2025-02-14YANCHENG INST OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411591701.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing high-temperature piezoelectric materials have not yet been proven to have acousto-electric conversion capabilities, especially at high temperatures.

Method used

TS-PAN nanofiber membranes were prepared by multi-step heat treatment method, and nanofiber membranes with conjugated trapezoidal structures were formed by electrospinning and thermal stabilization treatment, which were used as acoustic and electrical materials to develop acoustic and electrical energy collectors.

Benefits of technology

The TS-PAN nanofiber membrane exhibits excellent acoustoelectric conversion ability at high temperatures, can operate stably at a high temperature of 450°C, and can effectively convert acoustic energy into electrical energy under different acoustic frequency and sound pressure conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433827A_ABST
    Figure CN119433827A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-temperature-resistant nanofiber acoustoelectric material and a flexible high-temperature sound generator, can effectively and stably convert thermal sound waves into considerable electric energy at the temperature of 450 DEG C and can prepare piezoelectric devices, and relates to the technical field of sound-electric energy collection. The preparation method comprises the following steps: performing programmed heat treatment on an electrostatic spinning polyacrylonitrile nanofiber membrane to obtain a polyacrylonitrile piezoelectric material; the programmed heat treatment comprises a temperature rise stage and a constant temperature stage; the temperatures of the constant temperature stage are respectively 50 + / -10 DEG C, 100 + / -10 DEG C, 150 + / -10 DEG C, 200 + / -10 DEG C, 250 + / -10 DEG C, 260 + / -10 DEG C, 300 + / -10 DEG C, 350 + / -10 DEG C, 400 + / -10 DEG C and 450 + / -10 DEG C in sequence; and when the temperature of the programmed heat treatment is higher than 260 + / -10 DEG C, the programmed heat treatment is carried out in a protective atmosphere. Under single-frequency sound (118dB, 230Hz), a thin-film device (the working area is 3 * 3cm < 2 >) can generate an open-circuit voltage up to 118V and a short-circuit current (the power density is 392mW / m < 2 >) of 12muA, and the operation can be carried out in a wider temperature range of-450 DEG C to 450 DEG C. The polyacrylonitrile piezoelectric material prepared by the invention has excellent high-temperature resistance and thermal stability, and after the polyacrylonitrile piezoelectric material is prepared into a thermal-stability piezoelectric nano acoustoelectric device, the piezoelectric nano acoustoelectric device has excellent high-temperature resistance and thermal stability. The acoustoelectric energy collector can effectively and stably convert thermoacoustic waves into considerable electrical energy at a temperature of 450 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanogenerators, and in particular to a method for preparing a high-temperature resistant nanofiber acoustic-electric material and a flexible high-temperature acoustic generator. Background Art

[0002] The electrospun polyacrylonitrile (PAN) nanofiber membrane was thermally stabilized to cyclize the PAN chains and obtain a conjugated ladder structure, which showed excellent piezoelectricity at high temperatures up to 550°C. 2 The film can generate an open circuit voltage of 62V under mechanical compression and an output power density of 264W / m 2 However, whether such high-temperature piezoelectric materials have the ability to convert sound into electricity, especially at high temperatures, has not yet been confirmed in the research literature. Summary of the invention

[0003] The present invention is to use new acoustic-electric materials for developing acoustic-electric energy harvesters for various applications

[0004] The present invention first prepares TS-PAN nanofiber membrane. First, electrospinning is used to prepare PAN nanofiber membrane. Then a multi-step heat treatment is used to thermally stabilize the as-spun PAN nanofiber membrane. The program heat treatment includes a first heat treatment to a tenth heat treatment performed in sequence, and the temperatures of the first heat treatment to the tenth heat treatment are 50±5°C, 100±5°C, 150±5°C, 200±5°C, 250±5°C, 260±5°C, 300±5°C, 350±5°C, 400±5°C and 450±5°C respectively; when the treatment temperature is lower than 260°C, the PAN membrane is heated in an air atmosphere. However, when the temperature is higher than 260°C, the treatment is carried out in a nitrogen atmosphere to prevent degradation. After heat treatment, the nanofiber membrane still maintains good flexibility

[0005] The morphology of the PAN nanofibers in the present invention appears uniform and they are oriented along the rotation direction of the roller collector with an orientation angle within ±15°. The diameter of the as-spun PAN fibers is 490±40 nm. The fiber orientation is formed because the fibers are collected at a high speed (surface speed 4.5 m / s) during the electrospinning process. After stabilization treatment, the fibers become thinner by 380±30 nm, while the orientation remains almost unchanged because the fibers are fixed and stretched in the axial direction during the heat treatment.

[0006] The present invention also shows the FTIR spectrum images of PAN nanofiber membrane before and after heat treatment. The FTIR spectrum shows that the characteristic peaks of -CN, -C=N and pyridine structure are at 2243 cm -1 、1589cm -1 and 806cm -1After the stabilization treatment, these peaks changed significantly, confirming that chemical reactions occurred during the thermal treatment. The appearance of characteristic peaks related to -C=N- and -CN indicated the formation of pyridine structures. Solid 13 The C-NMR spectrum showed that the -CN, -CH and -CH2 peaks disappeared, while -C=N, -C=C and -C=CH appeared after heat treatment. These changes confirmed that PAN formed a conjugated structure after heat treatment. This thermal cyclization is consistent with previous reports on the thermal stability of PAN. DSC and TG analysis were performed to confirm that the cyclization was completed after the thermal stabilization treatment and there was no further weight loss when TS-PAN was heated at 260°C-450°C.

[0007] The WAXS spectrum also shows the difference in solid structure between PAN and TS-PAN nanofibers. Without thermal stabilization treatment, PAN nanofibers have a characteristic peak at 2θ≈17°, corresponding to the diffraction peak of PAN (100) crystal plane. However, for TS-PAN, a new broad diffraction peak appears at 2θ≈25°, and the peak position is consistent with the diffraction peak position of graphite (002) crystal plane, indicating that a graphite-like structure is formed inside the nanofiber. Due to the formation of a conjugated ladder structure after pre-oxidation.

[0008] The present invention also measured the Raman spectrum of the nanofibers. PAN without stabilization treatment has no obvious Raman characteristic peak. However, TS-PAN has a Raman characteristic peak at 1360 cm -1 and 1580cm -1 The D and G peaks are shown at , which are similar to carbon fibers. This can be explained by the in-plane stretching of the aromatic rings and the linear stretching of the -C=C bonds in the rings.

[0009] We used established methods to measure the piezoelectric properties of PAN nanofiber membranes at ambient and elevated temperatures. The electrical output values ​​of the devices showed little drop (or little change) as the temperature increased from room temperature to 450°C. These results confirm the excellent high-temperature piezoelectric properties of TS-PAN.

[0010] The small effect of operating temperature on the electrical output may be due to the stable piezoelectric properties of TS-PAN. Our previous study showed that the piezoelectric coefficient of TS-PAN remains almost unchanged over a wide temperature range up to its highest heat treatment temperature. Here, since the highest heat treatment temperature is 450°C, the piezoelectricity of our TS-PAN should be stable in the range of room temperature-450°C. The stable piezoelectricity leads to almost no change in the current output over a wide temperature range. However, the device made of untreated PAN film can only work stably up to 100°C. When the operating temperature is higher, such as 200°C, the device becomes unstable and can only work for 40 seconds before completely losing the energy conversion ability, indicating a narrow operating temperature range. These results are in good agreement with our previous report.

[0011] The present invention provides the preparation of piezoelectric devices and acoustic electric devices. TS-PAN nanofiber membrane (working area 3×3cm 2 , thickness 40μm) as the electroactive layer, two pieces of aluminum foil as electrodes, and PI film as the outer protective layer. Eight through holes (diameter 4.9mm) were cut on both the aluminum foil electrodes and the PI film to allow the nanofibers inside the device to directly receive sound.

[0012] The present invention also utilizes a device for testing acoustic-to-electric transduction. The sound waves cause the nanofibers to vibrate, and an external instrument records the electrical output produced by the nanofiber device, thus giving a typical V of a TS-PAN acoustic-to-electric device. oc and I sc Results. Under 230Hz single frequency 118dB SPL sound condition, the device produces 118V peak voltage and 12μA current ( Fig.10 and 11 ). When the sound frequency is kept at 230Hz and the SPL increases from 60dB to 90dB, V oc It is very low and almost remains constant with SPL. However, when SPL increases from 95dB to 118dB, the open circuit voltage output increases rapidly from 1.6V to 118V.

[0013] The present invention has shown that the sound frequency has an influence on the sound voltage output (i.e. V oc). At 118dB, the voltage output decreases as the sound frequency increases. Due to the limitations of the audio speaker used in this test, the lowest sound frequency obtained at 118dB is 230Hz. According to the output characteristics, the upper limit of the output (voltage greater than 5V) is determined to be 1200Hz. Therefore, the device frequency bandwidth is 230-1200Hz. Under the same conditions, the frequency bandwidth of the device made of unheated PAN nanofiber membrane is 230-950Hz. When the SPL is reduced to 110dB, the lowest frequency of the sound produced by the speaker is reduced to 170Hz. In this case, the bandwidth is changed to 170-950Hz. At 100dB, the minimum sound frequency is reduced to a lower value of 130Hz, and the corresponding bandwidth is 130-700Hz.

[0014] The output power of the TS-PAN nanofiber membrane was measured by connecting the device to external resistors with different resistance values. Under the sound conditions of 118 dB and 230 Hz, the voltage output increased with the increase of the resistance load, and the current output changed in the opposite trend to the voltage output. When the resistance value was 3.5 MΩ, the calculated maximum instantaneous peak power (P = UI) was 352.8 μW, and the corresponding peak power density was 39.2 μW / cm 2 When the SPL is 100 dB and 110 dB, the instantaneous peak power output is 176.3 μW and 201 μW, respectively. As we know, the energy device has the maximum power output when the external load is equal to the internal resistance of the device. Therefore, the internal resistance of the TS-PAN nanofiber membrane device is 3.5 MΩ.

[0015] We also estimated the energy conversion efficiency (η) using equations [40,42]:

[0016]

[0017] P Absorptuion =P Input -P Transmission (3)

[0018]

[0019] Here P Device is the power output of the acoustic-electric device, P Absorption is the acoustic energy absorbed by the nanofiber membrane device, P Input is the input sound energy, P Transmission is the output sound energy, f is the sound wave frequency, A is the effective emission area of ​​the speaker, P1 is the sound pressure at 118dB, P2 is the sound pressure of the sound, and ρ is the air density (1.204kg / m 3), c is the speed of sound in air (343.2m / s), and θ is the angle between the propagation direction and the surface normal. The formula for calculating the sound pressure (p) is:

[0020]

[0021] Where P ref is the reference sound pressure, which is a constant value of 0.00002Pa, and SPLdB is the SPL in dB. For the device made of TS-PAN nanofiber membrane, P2 is 116dB, which is equivalent to 36.9% of the sound energy absorbed by the nanofiber device. According to the above formula, the energy conversion efficiency of the device is about 86.6%.

[0022] The present invention further demonstrates that the TS-PAN membrane has excellent acoustic-to-electric conversion capabilities in high-temperature environments. Under the same sound source conditions but different temperatures (up to 450°C in air), the device shows similar electrical output.

[0023] As the temperature increased from room temperature to 450°C, the internal resistance decreased slightly from 3.9 MΩ to 3.6 MΩ, and the maximum power decreased from 352.8 μW to 312.0 μW. The small decrease in the internal resistance of the device can be attributed to the loss of electrons and the weakening of the signal due to the decrease in resistance at high temperature. For comparison, we also tested the acoustic-to-electric conversion of untreated PAN nanofibers. Under the same conditions, untreated PAN nanofibers can operate in a relatively narrow temperature range (room temperature-100°C). However, when the operating temperature was increased to 200°C, the membrane device lost its acoustic-to-electric activity within 44 seconds.

[0024] Our previous paper reported that electrospun PAN nanofiber membranes have strong piezoelectric properties and room-temperature acoustic-to-electric conversion capabilities. The acoustic-to-electric properties of PAN nanofiber membranes originate from their sound absorption and piezoelectric properties. Sound absorption causes nanofiber vibration and vibration deformation, resulting in piezoelectric polarization of the nanofibers. Charge transfer to external electrodes leads to electrical output. The electrical output depends on the piezoelectric material, the nanofiber structure, the dipoles formed within the nanofibers (caused by the chain structure) and between the nanofibers (caused by the charge centers), and the orientation of the dipoles. TS-PAN nanofiber membranes should follow a similar acoustic-to-electric conversion mechanism. Our previous study also showed that TS-PAN nanofiber membranes have high-temperature piezoelectric properties. However, acoustic-to-electric conversion of TS-PAN nanofiber membranes has not been reported before.

[0025] The acoustic-electric capability at high temperatures allows for direct conversion of thermoacoustic energy and indirect conversion of thermal energy into electrical energy. To harvest actual thermoacoustic energy using the TS-PAN device, the present inventors fabricated a micro thermoacoustic engine. A copper tube was used as a resonator and air was used as a working fluid. When the engine is heated on one side and cooled on the other, a temperature gradient is created. As a result, the air inside rapidly expands and compresses to generate sound waves.

[0026] When the present invention uses a gas torch as a heat source, the hot end temperature reaches 480°C. As a result, thermal sound with a main sound frequency of 358Hz is generated. When the TS-PAN device is placed 4mm away from the open end of the thermoacoustic engine, it is heated to a stable temperature of 280°C. Under thermoacoustic waves, the TS-PAN device generates a pulsed open-circuit voltage output of up to 102V. Measured by the external resistance loading method, the TS-PAN device can generate a peak power output of 291.2μW under the action of thermoacoustic waves, and the corresponding power density is 324mW / m 2 .

[0027] Measuring the sound pressure level at a distance of 4cm is difficult due to the high temperature thermal sound near the end of the engine. We can also measure the SPL at a father distance where the temperature is lower. At 15cm, the sound pressure of the thermal sound wave is 118.4dB.

[0028] The distance between the TS-PAN device and the open end of the engine shows the effect of energy conversion. As the distance increases from 2mm to 4mm (too small), the electrical output gradually decreases, and the current output shows similar results to the voltage output. When the distance is less than 2mm, the engine hot air flow is blocked, affecting the engine thermal sound conversion. On the other hand, when the distance exceeds 10mm, the sound is too weak to generate enough energy. At 4cm, the device reaches the highest voltage output, presumably because of the maximum sound pressure level under this condition.

[0029] For comparison, the present invention also tested the acoustic-to-electric conversion performance of untreated PAN nanofiber membranes and PVDF nanofiber membranes. Under the same conditions, the untreated PAN and PVDF devices had lower voltage output and shorter working life than the TS-PAN device. Both the untreated PAN and PVDF devices began to reduce electrical output within 21 seconds and completely lost output within 24 seconds. However, the TS-PAN nanofiber membrane device maintained a stable electrical output for at least 2 hours, verifying the excellent high-temperature stability.

[0030] It is important to note that the work of generating electricity from heat using thermoacoustic engines and nanofiber acoustoelectric devices has not been reported in the literature before. Our work is the first of its kind. This paper demonstrates the excellent high temperature stability of TS-PAN nanofiber membranes for thermoacoustic energy harvesting.

[0031] Polyacrylonitrile (PAN) itself is not a high-temperature polymer. Its glass transition temperature is about 102°C. However, after thermal stabilization, PAN has excellent thermal stability. Thermal stability is usually achieved by heat treatment at 260°C, so that its repeating units form a conjugated hexagonal ring structure. The rings in the molecular chain are connected to each other by sharing edges, forming a conjugated ladder structure. The ladder chains are also connected to each other throughout the material, and they also produce huge steric hindrance to prevent chain rotation or movement. As a result, the thermally stabilized PAN no longer melts and shows high thermal stability. This property has been widely used to develop flame-retardant fabrics. The unique ladder structure and remarkable thermal stability may be the reason why TS-PAN nanofibrous membranes have excellent acoustic and electrical capabilities at high temperatures.

[0032] The present invention also tested the possibility of converting thermoacoustic waves generated by other heat sources, such as alcohol burners, focused sunlight and candle flames. The main frequency of the thermoacoustic waves generated by alcohol flames is 358Hz, and the sound pressure level is 118.4dB, and the frequency of the thermoacoustic waves generated by sunlight is 355Hz, 118.5dB. In addition, we also used wet wipes to cool the thermoacoustic engine instead of using cooling tubes. The engine still produces 336Hz, 118.7dB. We found that as long as a temperature difference ΔT>100℃ is generated between the hot end and the cold end, the engine can generate thermoacoustic waves smoothly. Changes in heating or cooling methods have little effect on thermoacoustic conversion, but the thermoacoustic frequency changes slightly in the range of 330-360Hz and the sound pressure changes in the range of 117.5-119.1dB, and its thermoacoustic waves are very suitable for our TS-PAN acoustoelectric device.

[0033] Using our TS-PAN device, the versatility and applicability of the thermoacoustic waves generated by the thermoacoustic engine in the heat source can be used for sound-to-electric conversion, thus generating electricity from heat. As long as the temperature difference is large enough for the thermoacoustic engine to operate, the TS-PAN acoustic-electric device set up in the front can convert the thermoacoustic waves into electricity.

[0034] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] PAN solution (PAN solution: 12%, w / v) was prepared by dissolving PAN powder in DMF and heating at 50°C for 10 h. PAN nanofibrous membrane was prepared using a needle-type electrospinning machine. During the electrospinning process, the applied voltage, the flow rate of the polymer solution and the electrospinning distance were controlled at 22 kV, 0.5 mL / h and 15 cm, respectively. A grounded steel drum was used as a collector. The rotation speed of the drum was controlled at 1200 rpm. The as-spun PAN nanofibrous membrane was taken out of the steel drum and then heat-treated in a tubular furnace. During the heating process, the PAN membrane was fixed on a ceramic support.

[0037] The PVDF nanofibrous membranes were produced under the same electrospinning conditions without post-electrospinning heat treatment. To ensure an accurate comparison, we adjusted the PVDF concentration to make the fiber diameter similar to that of the heat-treated PAN nanofibrous membranes.

[0038] Figure 1 The process of preparing TS-PAN nanofibrous membranes is illustrated. First, electrospinning is used to prepare PAN nanofibrous membranes. Multi-step heat treatments are then used to thermally stabilize the as-spun PAN nanofibrous membranes. When the treatment temperature is below 260 °C, the PAN membranes are heated in an air atmosphere. However, when the temperature is above 260 °C, the treatment is performed in a nitrogen atmosphere to prevent degradation.

[0039] Test Example 1

[0040] Figure 2 This indicates that after heat treatment, the nanofiber membrane still maintains good flexibility. The PAN membrane prepared by the present invention exhibits excellent flexibility and mechanical stability.

[0041] Example 2

[0042] Device preparation

[0043] The piezoelectric device was fabricated according to a previously established method. The heat-treated PAN film (size, 3 × 3 cm 2 ; thickness 80 μm) was sandwiched between two metal foils. The device was then sealed on both sides with two mica plates (thickness 100 nm). Before measurement, the device was preheated to the target temperature.

[0044] The acoustic-electric device was fabricated according to the method we developed previously. 2 The electrospun PAN nanofiber membrane (thickness 40 μm) was sandwiched between two aluminum foils (20 μm) of the same size. The device was then sealed with a PI film (thickness 10 μm). The aluminum foil and PI film were cut using a laser cutter to have eight through holes (each with a diameter of 4.9 mm) in the middle area.

[0045] A micro thermoacoustic engine was prepared in the reference. In short, a copper tube (25 mm in diameter, 200 mm in length, and 1 mm in wall thickness) sealed at one end was used as a resonator. Steel wool was placed inside the copper tube (40 mm from the closed end of the copper tube and 30 mm thick inside the copper tube) to improve heat exchange. Near the open end, the copper tube was wrapped with another copper tube filled with cooling water. The sealed end was heated by a flame, while the other side was cooled by a cooling water pipe, generating a temperature gradient along the resonator, driving the internal air to expand and compress rapidly, thereby generating thermoacoustic waves.

[0046] Test Example 2

[0047] Use the fabricated device and piezoelectric material to achieve acoustic-electric conversion and measure its energy conversion characteristics

[0048] Piezoelectric energy conversion: A dedicated device, consisting of a pressure applicator, a heating plate (cast copper plus), an oscilloscope (internal resistance, 100 MΩ), a computer, and an electrochemical workstation, is used to measure the energy conversion characteristics of PAN piezoelectric devices at different temperatures. The PAN piezoelectric device is sandwiched between two heating plates. Prior to the measurement, the device is preheated to the target temperature. The membrane is then compressed and impacted with a pressure applicator. The voltage and current signals are simultaneously recorded with an oscilloscope and an electrochemical workstation.

[0049] Acousto-electric conversion: Dedicated equipment consisting of a commercial PC speaker as the sound source, an oscilloscope to record the voltage output, and an e-Corder 401 electrochemical workstation with a low-noise current preamplifier to record the current output is used to characterize the acoustic-to-electric conversion characteristics. Sound intensity and frequency are controlled by the audio test software. The acoustic-to-electric device is heated using a commercial heat gun and tested at different high temperature conditions. The voltage output is recorded by an oscilloscope. The current output is recorded by an e-Corder 401 electrochemical workstation with a low-noise current preamplifier. The sound pressure level (SPL) is measured by a sound level meter. The charging capacitor voltage is recorded by the electrochemical workstation.

[0050] Example 3

[0051] Figure 3 The SEM images shown were taken on a Hitachi S4800 scanning electron microscope. The diameter was analyzed based on the SEM images using a particle size analysis software. Thermogravimetric analysis (TGA) curves were measured using a thermogravimetric analyzer in a nitrogen atmosphere. The temperature range was 40-800°C (heating rate was 10°C / min). Differential scanning calorimeter (DSC) curves were measured in a nitrogen atmosphere using a differential scanning calorimeter. The temperature was controlled in the range of 25-300°C (rate 5°C / min). FTIR spectra were measured using an FTIR spectrophotometer in attenuated total reflectance (ATR) mode ( Figure 4Solid-state 13C-NMR spectra were measured on a 400WB solid-state NMR spectrometer. XRD patterns were measured on a diffractometer with Cu-Ka radiation at 40 kV and 30 mA. The samples were scanned in the 2θ range of 5-60°. Raman spectra were measured on a laser confocal Raman spectrometer ( Figure 5 ).

[0052] Test Example 3

[0053] Figure 6 The morphology of PAN nanofibers is shown. All fibers appear uniform and they are oriented along the rotation direction of the roller collector with an orientation angle within ±15°. The diameter of the as-spun PAN fibers is 490±40nm. The fiber orientation is formed because the fibers are collected at a high speed (surface speed 4.5m / s) during the electrospinning process. After stabilization treatment, the fibers become thinner by 380±30nm, while the orientation remains almost unchanged because the fibers are fixed and stretched in the axial direction during the heat treatment.

[0054] Figure 4 The FTIR spectra of PAN nanofiber membrane before and after heat treatment are shown. The FTIR spectra show that the characteristic peaks of -CN, -C=N and pyridine structure are at 2243 cm -1 、1589cm -1 and 806cm -1 After the stabilization treatment, these peaks changed significantly, confirming that chemical reactions occurred during the thermal treatment. The appearance of characteristic peaks related to -C=N- and -CN indicated the formation of pyridine structures. Solid 13 C-NMR spectrum showed that -CN, -CH, and -CH2 peaks disappeared, while -C=N, -C=C, and -C=CH appeared after heat treatment. These changes confirmed that PAN formed a conjugated structure after heat treatment. This thermal cyclization is consistent with previous reports on the thermal stability of PAN. We also performed DSC and TG analysis to confirm that the cyclization was completed after the thermal stabilization treatment and there was no further weight loss when heating TS-PAN at 260°C-450°C.

[0055] WAXS spectra show the difference in solid structure between PAN and TS-PAN nanofibers ( Figure 7 ). Without thermal stabilization treatment, PAN nanofibers have a characteristic peak at 2θ≈17°, corresponding to the diffraction peak of PAN (100) crystal plane. However, for TS-PAN, a new broad diffraction peak appears at 2θ≈25°, and the peak position is consistent with the diffraction peak position of graphite (002) crystal plane, indicating that a graphite-like structure is formed inside the nanofibers. Due to the formation of a conjugated ladder structure after pre-oxidation.

[0056] We also measured the Raman spectra of the nanofibers ( Figure 5 ). PAN without stabilization treatment has no obvious Raman characteristic peak. However, TS-PAN has a Raman peak at 1360 cm -1 and 1580cm -1 The D and G peaks are shown at , which are similar to carbon fibers. This can be explained by the in-plane stretching of the aromatic rings and the linear stretching of the -C=C bonds in the rings.

[0057] Example 4

[0058] The new acoustic-electric material can be used to develop acoustic-electric energy harvesters for various applications. The thermally stable polyacrylonitrile nanofiber membrane can form a new acoustic-electric material for thermoacoustic energy harvesting, medium- and low-grade waste heat recovery, and other high-tech applications.

[0059] Test Example 4

[0060] The thermoacoustic engine / TS-PAN acoustoelectric device combination provides a simple way to flexibly generate electricity from different heat sources, which is important for outdoor use. When solar heat is used as the heat source to run the thermoacoustic generator, the TS-PAN device produces an output of over 100V, which can directly power LCD electronics ( Figure 8 ), to drive the electronic scale or charge the lithium battery (a 7.4V, 300mAh lithium battery, the voltage rises to 1.05V after two hours; Fig. 9 ). In addition, the charged lithium battery can be used to run GPS, mobile phones and smart watches to assist outdoor adventures.

[0061] When using a candle flame as a heat source, the thermoacoustic engine / TS-PAN device can generate electricity at night. The power generated is comparable to that from other heat sources and can therefore be used for various purposes, such as charging lithium batteries.

[0062] Although here we use a micro-thermoacoustic engine as an example to demonstrate the feasibility of using TS-PAN acoustoelectric devices to harvest thermoacoustic energy, it should work for thermoacoustic waves generated by other thermoacoustic sources, and further designing multiple TS-PAN acoustoelectric devices for large-scale energy harvesting can generate electricity using industrial waste heat. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 Preparation process of thermally stable PAN nanofiber membrane;

[0064] Figure 2 Photographs showing the flexibility of PAN nanofiber membranes after thermal stabilization treatment;

[0065] Figure 3 SEM images of as-spun and thermally stabilized PAN nanofiber membranes (scale bar: 2 μm);

[0066] Figure 4FTIR spectroscopy;

[0067] Figure 5 Raman spectrum of PAN nanofiber membrane;

[0068] Figure 6 The morphology of PAN nanofibers is shown;

[0069] Figure 7 WAXS mode;

[0070] Figure 8 Digital photo of a commercial LED powered directly by a working TS-PAN device under thermoacoustic waves;

[0071] Fig. 9 LCD devices powered directly by TS-PAN devices under thermoacoustic waves (heat source, focused sunlight);

[0072] Fig.10 Open circuit voltage of TS-PAN acoustic-electric device under single-frequency sound (SPL 118 dB, sound frequency 230 Hz);

[0073] Fig.11 Short circuit current output.

Claims

1. A method for preparing a heat-stabilized polyacrylonitrile (TS-PAN) nanofiber membrane, comprising the following steps: PAN solution was prepared by dissolving PAN powder in DMF and heating at 50 °C for 10 h. PAN nanofiber membranes were prepared using a pin-type electrospinning machine.

2. The preparation method according to claim 1, characterized in that: The material selected was PAN powder and was dissolved by heating it at 50±5°C for 10±3 hours. The prepared PAN solution is 12%, w / v. During the electrospinning process, the applied voltage, the flow rate of the polymer solution and the working parameters of the electrospinning preferably include: the applied voltage is 15-30V, the flow rate of the polyacrylonitrile solution is 0.1-2mL / h, and the electrospinning distance is 5-25cm. A grounded steel drum is used as a collector. The rotation speed of the drum is controlled at 1200rpm. The as-spun PAN nanofiber membrane is taken out from the steel drum and then heat-treated in a tubular furnace. During the heating process, the PAN membrane is fixed on a ceramic support.

3. A method for preparing a piezoelectric device, comprising the following steps: The heat-treated PAN film was sandwiched between two metal foils. The device was then sealed on both sides with two mica sheets. The device was preheated to the target temperature before measurement.

4. The preparation method according to claim 3, characterized in that: The size of the heat-treated PAN film is (3±0.5)×(3±0.5)cm 2 ; Thickness is 70~90μm.

5. A method for preparing an acoustic-electric device, comprising the following steps: The electrospun PAN nanofiber membrane was sandwiched between two aluminum foils of the same size. The device was then sealed with a PI film. The aluminum foil and the PI film were cut using a laser cutter to have eight through holes in the middle area.

6. The preparation method according to claim 5, characterized in that: The size of electrospun PAN nanofiber membrane is (3±0.5)×(3±0.5)cm 2 , its thickness is 30-50μm; the size of the two aluminum foils is 10-30μm. The thickness of the PI film is 5-15μm. The diameter of each of the eight through holes cut out is 4.9±0.5mm.

7. A method for manufacturing a thermoacoustic engine, comprising the following steps: A copper tube sealed at one end is used as a resonator. Steel wool is placed inside the copper tube. Near the open end, the copper tube is wrapped with another copper tube filled with cooling water. The sealed end is heated by a flame, while the other side is cooled by a cooling water tube, creating a temperature gradient along the resonator, driving the internal air to expand and compress rapidly, thereby generating thermoacoustic waves.

8. The preparation method according to claim 7, characterized in that: The sealed copper tube has a diameter of 25 ± 10 mm, a length of 200 ± 10 mm, and a wall thickness of 1 ± 0.2 mm. The steel wool is 40 ± 5 mm away from the closed end of the copper tube, and the thickness of the copper tube is 30 ± 5 mm. This operation is to improve heat exchange.

9. The measurement operation of the energy conversion characteristics comprises the following steps: Piezoelectric Energy Conversion: A dedicated device, consisting of a pressure applicator, a heating plate, an oscilloscope, a computer and an electrochemical workstation, is used to measure the energy conversion characteristics of PAN piezoelectric devices at different temperatures. The PAN piezoelectric device is sandwiched between two heating plates. Prior to the measurement, the device is preheated to the target temperature. The membrane is then compressed and impacted with a pressure applicator. The voltage and current signals are simultaneously recorded with an oscilloscope and an electrochemical workstation. Acousto-electric conversion: Dedicated equipment consisting of a commercial PC speaker as the sound source, an oscilloscope to record the voltage output, and an e-Corder 401 electrochemical workstation with a low-noise current preamplifier to record the current output is used to characterize the acoustic-to-electric conversion characteristics. Sound intensity and frequency are controlled by the audio test software. The acoustic-to-electric device is heated using a commercial heat gun and tested at different high temperature conditions. The voltage output is recorded by an oscilloscope. The current output is recorded by an e-Corder 401 electrochemical workstation with a low-noise current preamplifier. The sound pressure level (SPL) is measured by a sound level meter. The charging capacitor voltage is recorded by the electrochemical workstation.

10. Other Characterized Devices SEM images were taken on a Hitachi S4800 scanning electron microscope. The diameter was analyzed based on the SEM images using a particle size analysis software. Thermogravimetric analysis (TGA) curves were measured using a thermogravimetric analyzer in a nitrogen atmosphere. The temperature range was 40-800°C, and the heating rate was 10°C / min. DSC curves were measured in a nitrogen atmosphere. The temperature was controlled at 25-300°C, and the rate was controlled in the range of 5±2°C / min. FTIR spectra were measured using an FTIR spectrophotometer in attenuated total reflection mode. Solid 13 C-NMR spectra were measured on a 400WB solid-state NMR spectrometer. XRD patterns were measured on a diffractometer with Cu-Ka radiation at 40 kV and 30 mA. The samples were scanned in the 2θ range of 5-60°. Raman spectra were measured on a laser confocal Raman spectrometer.

11. Only by using the preparation method and device according to claims 1 to 10 can the polyacrylonitrile piezoelectric material convert sound energy into electrical energy at high temperature, and measure and collect the obtained stable electrical energy.

12. According to claim 11, this new type of acoustic-electric material can be used to develop acoustic-electric energy harvesters for various applications.

Citation Information

Patent Citations

  • Polyacrylonitrile piezoelectric material, preparation method and application thereof, and flexible piezoelectric nano-generator

    CN113564804A